THE TRAGEDY OF THE PERIOD AND THE PERSON IN “NIGHT AND DAY” (The Conference Hub, 2025)
The article discusses social life, political processes and moral pressure in the novel “Night and Day”. Several assumptions are made about the continuation of the novel. It is noted that the diversity of images in the work is clearly visible.